2021
DOI: 10.1136/jclinpath-2020-207356
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of SARS-CoV-2 antibody responses pre-COVID-19 and post-COVID-19 convalescent plasma transfusion in patients with severe respiratory failure: an observational case–control study

Abstract: AimsWhile the SARS-CoV-2 pandemic may be contained through vaccination, transfusion of convalescent plasma (CCP) from individuals who recovered from COVID-19 (CCP) is considered an alternative treatment. We investigate if CCP transfusion in patients with severe respiratory failure increases plasma titres of SARS-CoV-2 antibodies and improves clinical outcomes.MethodsPatients with COVID-19 (n=34) were consented for CCP transfusion and serial blood draws pretransfusion and post-transfusion. Plasma SARS-CoV-2 ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
(29 reference statements)
0
6
0
2
Order By: Relevance
“…Regarding the comparison of immune response between CP recipients and non-CPtreated patients, Klein et al showed similar Spike-RBD kinetics between a cohort of 34 CP recipients compared to a matched control group; however, in this study, CP was given at a median of 11 days from symptom onset. Delayed intervention might explain the null effect on CP kinetics [33]. Similarly, the PlasmAr study showed increased antibody levels only on day 2 following CP infusion compared to controls, whereas no differences were observed at the subsequent time points evaluated [9].…”
Section: Discussionmentioning
confidence: 92%
“…Regarding the comparison of immune response between CP recipients and non-CPtreated patients, Klein et al showed similar Spike-RBD kinetics between a cohort of 34 CP recipients compared to a matched control group; however, in this study, CP was given at a median of 11 days from symptom onset. Delayed intervention might explain the null effect on CP kinetics [33]. Similarly, the PlasmAr study showed increased antibody levels only on day 2 following CP infusion compared to controls, whereas no differences were observed at the subsequent time points evaluated [9].…”
Section: Discussionmentioning
confidence: 92%
“…Randomized controlled trials to evaluate COVID-19 convalescent plasma for prophylaxis and early treatment in adults are currently underway ( 13 , 14 ). Studies evaluating antibody kinetics of convalescent plasma have been conducted in infected individuals who developed endogenous anti–SARS-CoV-2 antibodies ( 15 ). However, antibody kinetics in SARS-CoV-2–exposed individuals or those early in disease and without endogenous antibody production, where antibody therapies are most useful ( 11 ), have not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the PennCCP2 trial (US) 44 found a benefit in the primary clinical endpoint of disease severity and 28-day mortality, and a double-blind RCT study by O'Donnell et al, (US and Brazil) 45 found CCP was not associated with significant improvement in day 28 clinical status, but was associated with significantly improved survival. Observational studies [46][47][48][49][50][51][52][53][54] have reported mixed findings, but generally suggest that efficacy is more likely with high titer CCP in earlier and less severe disease, [46][47][48][49][50][51][52][53] or when used in those with impaired immunity. [55][56][57] Interpretation of RCT data, including those in recent metaanalyses, 58,59 is made challenging for multiple reasons: 1) the use of either untitered plasma or plasma qualified by serologic testing alone,…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the PennCCP2 trial (US) 44 found a benefit in the primary clinical endpoint of disease severity and 28‐day mortality, and a double‐blind RCT study by O'Donnell et al, (US and Brazil) 45 found CCP was not associated with significant improvement in day 28 clinical status, but was associated with significantly improved survival. Observational studies 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 have reported mixed findings, but generally suggest that efficacy is more likely with high titer CCP in earlier and less severe disease, 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 or when used in those with impaired immunity. 55 , 56 , 57 …”
Section: Discussionmentioning
confidence: 99%